PENGARUH BOARD INDEPENDENCE, AUDIT COMMITTEE, DAN MANAGERIAL OWNERSHIP TERHADAP SUSTAINABILITY REPORTING PADA ASEAN CORPORATE GOVERNANCE SCORECARD - Wiwi Idawati; Ayunda Novita Hanifah (Universitas Multimedia Nusantara, 2022)
Abstract— This study aims to examine the influence of board independence, audit committee, and managerial ownership on sustainability reporting based on united nations sustainable development goals (un_sdgs). This study uses data from Public Companies in Indonesia based on the ASEAN Corporate Governance Scorecard listed on the Indonesia Stock Exchange. The hypothesis in this study was tested with descriptive statistics and panel data regression anlysis. The results of this study prove that board Independence has a negative effect on Sustainability Reporting. The results of the Audit Committee and Managerial Ownership have no correlation with Sustainability Reporting. Keywords: Board Independence; Audit Committee; Managerial Ownership; Sustainability Reporting.